THE INFLUENCE OF ECONOMIC LITERACY, FINANCIAL LITERACY AND SELF CONTROL ON CONSUMER BEHAVIOR AMONG SHOPEE USERS AMONG MUHAMMADIYAH UNIVERSITY STUDENTS IN SIDOARJO - Juanita, Senja Putri; Abidin, Fityan Izza Noor (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The purpose of this study is to provide knowledge whether the variables of economic literacy, financial literacy and self-control have an effect on consumptive behavior. Method: This study uses Final Semester Accounting Study Program students of Muhammadiyah University of Sidoarjo as a population with a total of 117 people. Using primary data from questionnaires as a method of data collection. Data analysis techniques in this study consist of validity tests, reliability tests, multiple linear regression analysis, and hypothesis testing in the form of t-tests using SPSS version 26. Results: This study provides results that economic literacy and self-control have a significant positive effect on student consumptive behavior and financial literacy has a significant negative effect on student consumptive behavior. Novelty: It is hoped that this study will provide positive benefits for all parties.